Marcas da história de vida na constituição profissional do coordenador pedagógico: um estudo a partir de narrativas de experiências como dispositivos de pesquisa-formação - Tahan, Simone Pannocchia (2019)
Starting with the premise that, in formation processes, adults constitute themselves through their own experiences, backgrounds and events that surrounded their existence; this research aims to identify formative experiences of the pedagogic coordinators’ professional constitutional process that release narratives produced in the context of a reflection group. From the hypothesis that narrating individual experiences can promote a better comprehension of the individuals and the possibility of a more conscious professional performance, this study is structured in the perspective of a research training, based on the theoretical references of the (auto)biographical approach (PINEAU, 2005). The methodology is constituted of work sessions that support the production of narratives and, furthermore, the considerations produced in a group of professionals, in a way the narratives of experience of coordinators integrate the analysis corpus as much as a field diary written by the researcher which has the considerations made in the reflection group. The analysis was built from the concept of interpretative-comprehensive analysis as promoted by Souza (2004). The participants who integrate this research training are four pedagogic coordinators, who perform in different stages of basic education in Brazil, namely: Ensino Fundamental I, Ensino Fundamental II and Ensino Médio. A private institution based in Greater São Paulo area, was the context chosen to the study. The theoretical framework is supported by the productions of Ferrarotti (2010); Nóvoa (2013, 2014); Passeggi (2011, 2016); Souza (2006, 2014); Passeggi e Souza (2017); Delory- Momberger (2006, 2011, 2012); Josso (2008, 2010, 2014); Almeida & Placco (2009); Placco, Almeida & Souza (2015). The results indicate that narratives of experiences can become powerful devices in the process of adult formation, once they allow reflections about the professional constitution. The formative experiences revealed in the narratives indicate the reasons why each coordinator has entered the Educational area and they facilitate the comprehension of how professional formation and performance are surrounded by personal and familiar impressions and milestones